Generalization of a genetic risk score for time to first albuminuria in children with sickle cell anaemia: SCCRIP cohort study results. (16th June 2021) - Rashkin, Sara R.; Rampersaud, Evadnie; Kang, Guolian; Ataga, Kenneth I.; Hankins, Jane S.; Wang, Winfred; Estepp, Jeremie H.; Weiss, Mitchell J.; Lebensburger, Jeffrey; Zahr, Rima S.
Summary: Albuminuria predicts kidney disease progression in individuals with sickle cell anaemia (SCA); however, earlier prediction of kidney disease with introduction of reno‐protective therapies prior to the onset of albuminuria may attenuate disease progression. A genetic risk score (GRS) for SCA‐related nephropathy may provide an improved one‐time test for early identification of high‐risk patients. We utilized a GRS from a recent, large, trans‐ethnic meta‐analysis to identify three single nucleotide polymorphisms that associate individually and in a GRS with time to first albuminuria episode in children with SCA.